(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
Violence against women is a complex social phenomenon, related to patriarchal power, based on the exploitation of unpaid domestic work, as well as the sexual and reproductive exploitation of women. Femicide is the maximum exponent of violence against women, generally committed by men close to the victim. This is a cartographic experience report that deals with violence against women and feminicide as an exercise of hatred against insubordination, based on the experience of the presentations of the show Those – A diet to fit into the world, by Grupo Manada Teatro, which was presented at the Ceará and Pará, as well as workshops and meetings with women during the caravan.